High-throughput synthesis and optimization of ionizable lipids through A3 coupling for efficient mRNA delivery - Jingjiao Li; Jie Hu; Danni Jin; Haonan Huo; Ning Chen; Jiaqi Lin; Xueguang Lu (Journal of Nanobiotechnology)
Abstract Background The efficacy of mRNA-based vaccines and therapies relies on lipid nanoparticles (LNPs) as carriers to deliver mRNA into cells. The chemical structure of ionizable lipids (ILs) within LNPs is crucial in determining their delivery efficiency. Results In this study, we synthesized 623 alkyne-bearing ionizable lipids using the A3 coupling reaction and assessed their effectiveness in mRNA delivery. ILs with specific structural features—18-carbon alkyl chains, a cis-double bond, and ethanolamine head groups—demonstrated superior mRNA delivery capabilities. Variations in saturation, double bond placement, and chain length correlated with decreased efficacy. Alkynes positioned adjacent to nitrogen atoms in ILs reduced the acid dissociation constant (pKa) of LNPs, thereby hindering mRNA delivery efficiency. Conversion of alkynes to alkanes significantly enhanced mRNA delivery of ILs both in vitro and in vivo. Moreover, combining optimized ILs with cKK-E12 yields synergistic LNPs that showed markedly augmented mRNA expression levels in vivo. Conclusions Overall, our study provides insights into the structure–function relationships of ILs, providing a foundation for the rational design of ILs to enhance the efficacy of LNPs in mRNA delivery. Graphical Abstract